THE IMPACT OF SOME ECONOMIC VARIABLES ON ECONOMIC GROWTH IN IRAQ FOR THE PERIOD 2003-2022: A STANDARD STUDY - Ahmed Jeber Salem Al-Abouda; Ahmed Jasim Mohammed Al-Matury; Shahad Jasim Mohammed (Journal of Economic and Economic Policy, 2026)
Objective: Studying the economic variables influencing economic growth in Iraq for the period 2003-2022 is important for Iraq, especially after the events of 2003 and the accompanying changes in economic policy. Therefore, the research aims to understand the impact of these variables on the path of economic development in Iraq. Method: To address the research problem, economic measurement was used through the utilization of Eviews 12 software and some tests, including the unit root test. The time series data were transformed into logarithms, and it was found that the statistical value was not significant because the PRO value was less than 0.005. As a result, the first difference was taken where the time series stabilized. The Box-Jenkins method was used, and then the best model was selected to study the case of economic growth for the Iraqi economy until 2032. Results: The analysis shows that after stabilizing the time series data, the selected Box-Jenkins model effectively captured the dynamics of economic growth in Iraq. The results indicate that key economic variables significantly influence GDP growth trends, and the forecast suggests a steady growth trajectory for the Iraqi economy up to 2032 under current policy conditions. Novelty: The study applies the Box-Jenkins method combined with Eviews 12 software to model and forecast economic growth in Iraq until 2032, considering the impact of economic variables after the events of 2003 and subsequent policy changes.